Comparison of the antiarrhythmic potential of doxapram and its metabolite ketodoxaparam. (3rd October 2022) - Kraft, M; Wiedmann, F; Foerster, K I; Sauter, M; Paasche, A; Blochberger, P L; Yesilgoez, B; L'hoste, Y; Arif, R; Warnecke, G; Karck, M; Frey, N; et al.
Abstract: Background: A few years ago, the TASK-1 channel has been established as a potential new target for the therapy of atrial fibrillation (AF). In the heart, TASK-1 is almost exclusively expressed in the atria and is significantly upregulated in AF patients. Therefore, it plays an important role in the shortening of the atrial action potential observed during AF, making TASK-1 a promising target for AF therapy. This could be proven in a porcine model of persistent AF in which an intravenous application of the TASK-1 inhibitor doxapram led to a termination of AF and the restoration of sinus rhythm (SR). Doxapram's metabolite ketodoxapam is described in the literature as being active with limited data available on its usage. Therefore, the effect of ketodoxapram on TASK-1 and its possible use in AF therapy still needs to be investigated. Purpose: The purpose of the present study was to assess the potential of ketodoxapram in the termination of AF. Furthermore, a comparison between doxapram and ketodoxapram was performed based on electrophysiological and pharmacological data. Methods: UPLC-MS/MS assays were developed and validated for the measurement of doxapram and ketodoxapram in porcine plasma and brain tissue. Using these assays, the pharmacokinetics of both substances, after intravenous injections of 1 mg/kg, were determined in pigs. Furthermore, brain and plasma concentrations were measured to assess brain-to-plasma ratios. A porcine AF model was used to estimate the antiarrhythmic potential. Electrophysiological properties were evaluated, using two-electrode voltage clamp experiment on Xenopus laevis oocytes which heterologously expressed atrial potassium channels, to calculate the effect of doxapram and ketodoxapram on channel function. Furthermore, whole-cell patch clamp measurements were performed on isolated human cardiomyocytes. Results: Doxapram and ketodoxapram showed strong inhibitory effects on TASK-1 (IC50 1.0 μM and 0.8 μM) and TASK-3 (5.9 μM and 1.5 μM), but no significant effect on the other measured ion channels. The maximal inhibition on TASK-1 was 96%. The brain-to-plasma ratio for doxapram (0.58) was almost ten-fold higher than for ketodoxapram (0.065), hinting at a reduced crossing of the blood-brain barrier (BBB) for ketodoxapram. The terminal half-life (t1/2) of ketodoxapram (1.71 h) was longer and the maximal concentration (Cmax; 4, 604 ng/ml) was higher than for doxapram (1.38 h; 1, 780 ng/ml). In a porcine model of AF, ketodoxapram led to a significantly reduced AF burdens comparable to doxapram. Conclusions: Doxapram and ketodoxapram both show strong inhibitory effects on TASK-1, making them good candidates for a TASK-1 based AF therapy. Ketodoxapram with its longer t1/2, reduced crossing of the BBB and higher Cmax points towards a possible superiority in the treatment of AF compared to doxapram. Studies in a porcine AF model showed promising results for the use of doxapram and ketodoxapram in AF therapy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Research Foundation